2002
DOI: 10.1590/s1413-86702002000600004
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureus bacteremia: comparison of two periods and a predictive model of mortality

Abstract: Staphylococcus aureus is an important pathogen causing bacteremia, primarily affecting hospitalized patients. We studied the epidemiology of S. aureus bacteremia, comparing two periods (early and mid 1990s) and developed a predictive model of mortality. A nested case-control was done. All 251 patients over 14 years old with positive blood cultures for S. aureus were selected. MRSA (methicillin resistant S. aureus) was isolated in 63% of the cases. When comparing the two periods MRSA community-acquired bacterem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…A study performed in south-east Brazil reported an increasing incidence of community-acquired bacteraemia due to MRSA. 25 In a recent report of 17 hospitals in Australia, 12% of community-onset episodes were MRSA. 26 In the present study, all patients with community-acquired MRSA bacteraemia had received healthcare assistance.…”
Section: Discussionmentioning
confidence: 99%
“…A study performed in south-east Brazil reported an increasing incidence of community-acquired bacteraemia due to MRSA. 25 In a recent report of 17 hospitals in Australia, 12% of community-onset episodes were MRSA. 26 In the present study, all patients with community-acquired MRSA bacteraemia had received healthcare assistance.…”
Section: Discussionmentioning
confidence: 99%
“…They found no significant differences in the mortality rates. Based on logistic regression, septic shock, source of bacteremia and methicillin resistance were found to be positively associated with subsequent mortality [18].…”
Section: The Studiesmentioning
confidence: 99%
“…Although data can be found in the literature indicating an increasing incidence of community-acquired oxacillin-resistant S. aureus infections, it can be seen that most studies do not clearly show the criteria used to define community-acquired infection, which is frequently taken as an infection detected by culture within 48 or 72 hours of admission to hospital [2,5]. Based on the criteria adopted in our study, and in view of the greater accuracy of the data resulting from the prospective nature of the study, we did not detect any cases of community-acquired resistant S. aureus.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study carried out in the Hospital São Paulo showed that 4.4% of the cases of oxacillinresistant S. aureus bacteremias seen there from 1991-92 were community-acquired, whereas the percentage was 15.9% for 1995-96, indicating an increasing trend in our community [5].…”
mentioning
confidence: 80%
See 1 more Smart Citation